Impact of Food Physical Properties on Oral Drug Absorption: A Comprehensive Review - Wang Z; Xu W; Liu D; Li X; Liu S; Wu X; Wang H (Drug Design, Development and Therapy)
Ziyang Wang,1 Wen Xu,2 Dan Liu,3 Xiuqi Li,1 Shupeng Liu,1 Xiaofei Wu,1 Hongyun Wang1 1Clinical Pharmacology Research Center, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, People’s Republic of China; 2CSPC Zhongqi Pharmaceutical Technology (Shijiazhuang) Co., Ltd, Shijiazhuang, People’s Republic of China; 3College of Pharmacy, Shenyang Pharmaceutical University, Shenyang, People’s Republic of ChinaCorrespondence: Hongyun Wang, Clinical Pharmacology Research Center, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, People’s Republic of China, Tel +8610-69154637, Email wanghy@pumch.cnAbstract: Food-Drug Interaction (FDI) refers to the phenomenon where food affects the pharmacokinetic or pharmacodynamic characteristics of a drug, significantly altering the drug’s absorption rate or absorption extent. These Interactions are considered as a primary determinant in influencing the bioavailability of orally administered drugs within the gastrointestinal tract. The impact of food on drug absorption is complex and multifaceted, potentially involving alterations in gastrointestinal physiology, increases in splanchnic blood flow rates, and shifts in the gut microbiota’s composition. Up to now, extensive research has focused on the interactions between food composition (such as proteins, fats, and vitamins) and drug absorption. In contrast, the impact of food physical properties (such as viscosity, volume, and pH) has received less attention in drug development. This article reviewed the impact of food properties on oral drug absorption based on a comprehensive literature search, focusing on the influence of food volume and food viscosity. From the perspective of pharmacokinetics, we examined interaction trends between food properties and drugs across different classification based on the Biopharmaceutics Classification System (BCS). In addition, we introduced the practical application of physiologically based pharmacokinetic (PBPK) modeling in predicting oral drug absorption under the influence of food Properties.Plain language summary: In the development of new drugs, understanding how food affects drug absorption is crucial. Although scientists have deeply studied the role of food components–such as proteins, fats, and carbohydrates–in drug absorption, the impact of food’s physical properties, like viscosity, volume, and temperature, on drug safety is often overlooked. Dietary differences across cultures, such as the sticky porridge and steamed buns in China versus bread and milk in the West, suggest that food properties may differentially affect drug absorption. We emphasize the key role of food properties in drug absorption and review how these properties influence gastrointestinal function and drug bioavailability. Additionally, we discuss the specific interactions between different types of drugs and food properties, emphasizing the importance of incorporating food properties into the construction of drug absorption models.Keywords: food properties, food-drug interactions, PBPK models, biopharmaceutics classification system